CrRLK1L receptor‐like kinases HERK1 and ANJEA are female determinants of pollen tube reception. (23rd December 2019) - Galindo‐Trigo, Sergio; Blanco‐Touriñán, Noel; DeFalco, Thomas A; Wells, Eloise S; Gray, Julie E; Zipfel, Cyril; Smith, Lisa M
Abstract: Communication between the gametophytes is vital for angiosperm fertilisation. Multiple Cr RLK1L‐type receptor kinases prevent premature pollen tube burst, while another Cr RLK1L protein, FERONIA (FER), is required for pollen tube reception in the female gametophyte. We report here the identification of two additional Cr RLK1L homologues, HERCULES RECEPTOR KINASE 1 (HERK1) and ANJEA (ANJ), which act redundantly to promote pollen tube growth arrest at the synergid cells. HERK1 and ANJ localise to the filiform apparatus of the synergid cells in unfertilised ovules, and in herk1 anj mutants, a majority of ovules remain unfertilised due to pollen tube overgrowth, together indicating that HERK1 and ANJ act as female determinants for fertilisation. As in fer mutants, the synergid cell‐specific, endomembrane protein NORTIA (NTA) is not relocalised after pollen tube reception; however, unlike fer mutants, reactive oxygen species levels are unaffected in herk1 anj double mutants. Both ANJ and HERK1 associate with FER and its proposed co‐receptor LORELEI (LRE) in planta . Together, our data indicate that HERK1 and ANJ act with FER to mediate female–male gametophyte interactions during plant fertilisation. Synopsis: The Cr RLK1L receptor kinases HERK1 and ANJ are genetically redundant during pollen tube reception in Arabidopsis . Both proteins interact with the Cr RLK1L receptor FER and its putative co‐receptor LRE, however the role of FER in fertilisation extends to production of reactive oxygen species in ovules while HERK1 and ANJ are not involved in this process. Double mutants of HERK1 and ANJ produce fewer seeds as pollen tube overgrowth occurs in the majority of ovules in a maternally‐controlled phenotype. HERK1 and ANJ are both expressed in the synergid cells, where other fertilisation components in the form of Cr RLK1L receptor FERONIA, its co‐receptor LORELEI, and downstream protein NORTIA are also located. Kinase activity of HERK1 and ANJ is not required for complementation of the pollen tube reception phenotype. HERK1 and ANJ interact with FER and LRE. Unlike FER, HERK1 and ANJ are not required for pre‐fertilisation production of reactive oxygen species. Abstract : The Cr RLK1L receptor kinases HERK1 and ANJ are genetically redundant during pollen tube reception in Arabidopsis . Both proteins interact with the Cr RLK1L receptor FER and its putative co‐receptor LRE and contribute to NTA relocalisation but not to ROS production.